Sosialisasi Pemberdayaan Terhadap Keluarga Penerima Manfaat Program Keluarga Harapan Melalui Kewirausahaan di Kelurahan Kedondong Raye - Dewi, Inne Miftah; Syaparman; Al Adawiyah, Robiah (Yayasan Kawanad, 2023)
Socialization activities are one of the media for conveying information to the public. By sharing information and education that useful for PKH Beneficiary Families in the Kedondong Raye Village by conducting socialization on empowerment of PKH beneficiaries through entrepreneurship in digital era. The purpose of this socialization is to provide socialization to PKH beneficiaries in building personal branding in starting a business dan fostering an entrepreneurial spirit by utilizing digital technology through social media Whatsapp, Facebook, and Instagram. The implementation of socialization activities is carried out by direct exposure to digital technology beneficiaries in entrepreneurship and the conducting demonstrations and practices to the participants. The result of this socialization is providing participants with an understanding of how to start a business and entrepreneurship by utilizing digital technology by taking advantage of existing opportunities so that they can create business dan work opportunities for those around them.